Implementasi Permainan Pickleball Sebagai Media Pembelajaran Pendidikan Jasmani dalam Meningkatkan Keterampilan Motorik Kasar Siswa Sekolah Dasar - Nofulan Adyani; Anung Priambodo; Sapto Wibowo (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aimed to analyze the effect of implementing Pickleball on improving students’ gross motor skills in physical education. A quantitative approach with a quasi-experimental one-group pretest–posttest design was used. The research sample consisted of 45 fourth-grade students from SDN Suko 2 Sidoarjo, selected through purposive sampling. The instrument used was a gross motor skill test covering balance, coordination, speed, and large muscle strength. Data were analyzed using descriptive statistics, prerequisite tests, and a Paired Sample t-Test at a 0.05 significance level. The results showed a significant improvement in gross motor skills, with mean scores increasing from 68.24 to 84.67 (t = -11.258; p = 0.000). It was concluded that Pickleball effectively enhances gross motor skills and serves as an engaging, adaptable learning medium in the Merdeka Curriculum. Keywords: Pickleball, physical education, gross motor skills, elementary school students